Meningkatkan Akurasi Layanan dan Mengurangi Penundaan dengan ASD Tug MV. Ace Guard: Analisis Studi Kasus - Welem Ada (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
This research article examines the process of delaying service at West Opel through observations made while working on board the ship. This study focuses on two main factors that affect the efficiency of the towage process: the delay in maneuvering the ship and the time it takes. The observations highlight the impact of the power limitations of conventional tugs compared to ASD tug systems, particularly MVs. Ace Guard. This finding reveals that the insufficient power of a conventional vessel impedes the smooth maneuverability of the vessel, so that the ASD tug has to adjust its power to match that of a conventional tug and maintain the correct position while the vessel departs. In addition, this study emphasizes the significant duration of time involved in the towage process, taking into account the coordination between ASD tugs and conventional tugs. This research concludes that these factors contribute to a slower and more time consuming procrastination process. The case studies presented provide valuable insights for optimizing and increasing the efficiency of service operations in a similar maritime environment.